An electrochemical impedance model of lithium-ion battery for electric vehicle application. (June 2022) - Zhang, Qi; Wang, Dafang; Yang, Bowen; Dong, Haosong; Zhu, Cheng; Hao, Ziwei
Highlights: The series structure of the model is derived by simplifying the ion transport path. A pipeline model is used to describe lithium ions transport in electrolyte phase. Impedance expressions of internal processes of lithium ion batteries are derived. The relationships between electrochemical parameters and impedances are discussed. Abstract: Electrochemical Impedance Spectroscopy (EIS), as powerful technique of describing electrochemical processes inside lithium-ion batteries (LiBs), has been widely studied for many applications, such as state-of-health (SOH) estimation and degradation diagnostic. To achieve the quantitative analysis on internal processes of LiBs in the electric vehicle (EV) application, a series electrochemical impedance model is developed in this paper. Two novel simplifications on the lithium ion transport path and the electrolyte diffusion make the impedance model have high computational efficiency and more likely to achieve on-board applications. The proposed model has been verified by comparing with measured EISs of three types of LiBs under different state-of-charge (SOC), which proves that it has high simulation accuracy and adaptability. Besides, we analyze the relationship between model parameters and the impedance and extracts some change rules of parameters, all these rules could provide theoretical guidance for the parameter identification of LiBs.